2013
DOI: 10.1007/s11356-013-1680-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate facilitates cadmium uptake, transport and accumulation in the hyperaccumulator Sedum plumbizincicola

Abstract: The aims of this study are to investigate whether and how the nitrogen form (nitrate (NO 3 -) versus ammonium (NH 4 + )) influences cadmium (Cd) uptake and translocation and subsequent Cd phytoextraction by the hyperaccumulator species Sedum plumbizincicola. Plants were grown hydroponically with N supplied as either NO 3 -or NH 4 + . Short-term (36 h) Cd uptake and translocation were determined innovatively and quantitatively using a positron-emitting 107 Cd tracer and positron-emitting tracer imaging system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 51 publications
4
23
1
Order By: Relevance
“…However, in hydroponic experiments, supplying NO 3 − doubled Cd concentration in the shoots of Noccaea caerulescens, compared with NH 4 + supply (Xie et al 2009). Similar results were found for Sedum plumbizincicola in solution culture; NO 3 − stimulated Cd uptake by roots, xylem loading, shoot-to-root translocation, and uploading to the leaves and thus enhanced Cd phytoextraction (Hu et al 2013). Monsant et al (2008) showed that NO 3 − nutrition improved Zn phytoextraction in solution culture by increasing the biomass and Zn concentration of shoots of N. caerulescens.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, in hydroponic experiments, supplying NO 3 − doubled Cd concentration in the shoots of Noccaea caerulescens, compared with NH 4 + supply (Xie et al 2009). Similar results were found for Sedum plumbizincicola in solution culture; NO 3 − stimulated Cd uptake by roots, xylem loading, shoot-to-root translocation, and uploading to the leaves and thus enhanced Cd phytoextraction (Hu et al 2013). Monsant et al (2008) showed that NO 3 − nutrition improved Zn phytoextraction in solution culture by increasing the biomass and Zn concentration of shoots of N. caerulescens.…”
Section: Introductionsupporting
confidence: 75%
“…The results are inconsistent with those of Xie et al (2009) and Hu et al (2013). By using a positronemitting 107 Cd tracer, Hu et al (2013) showed that Cd transport was 1.5-fold and 3.7-fold faster in the roots and shoots, respectively, in the Cd hyperaccumulator S. plumbizincicola supplied with NO 3 − than with NH 4 + . The concentration of Cd was 2.63 times higher in shoots of the NO 3 − -than NH 4 + -fed plants in nutrient solution.…”
Section: Discussionmentioning
confidence: 72%
“…The Cd and P phytoavailability of kangkong ( Ipomoea aquatica Forsk.) with Alfred stonecrop ( Sedum alfredii Hance) can be induced while inoculated with arbuscular mycorrhizal fungi (Hu et al 2013 ).…”
Section: Phytoavailability Of Metalsmentioning
confidence: 99%
“…Whereas, in case of hyperaccumulators roots effi ciently transport metals to the shoots, e.g., in case of Sedum alfredii ecotype, xylem plays an important role in Cd uptake as compared to the non-hyperaccumulating ecotypes (Lu et al 2009 ). The translocation of Cd uptake and Cd phytoextraction has been recently studied by Hu et al ( 2013 ) in another species of Sedum plumbizincicola . In this study they found that the rate of Cd uptake was more from roots to the shoots when NO 3-treatment was given.…”
Section: Transportion From Root To Shootmentioning
confidence: 99%
“…Therefore,the presence of Cd can also not influence MT expression, this was described in tomato (present work and OUZIAD et al, 2005) and sugarcane (GUO et al, 2013), only the combination Nitrogen is an essential macronutrient, responsible for the biosynthesis of all aminoacid, protein and enzymes, despite of the decrease in nitrogen content in the presence of the bacteria, inoculated plants grew more, presenting a higher biomass, and consequently a total protein and nitrogen higher than non inoculated plants. Hu et al (2013) reported that nitrate (not ammonium) induce Cd and Zn uptake (increasing fitoextraction). In the pot assay of the present work, we used a fertilizer with nitrate, enhancing Cd uptake, finding a high concentration of Cd in leaves, the addition of SCMS54:gfpdecreased Cd absorption, decreasing phytoextraction potential, but on the other hand, increasing plant tolerance.…”
Section: And Bymentioning
confidence: 99%